Modulation of the African-Indian rainfall relationship by the thermal variability over the Mediterranean Sea in northern summer. - (:unkn) unknown (My University, 2013)
This statistical study stresses the relationship between different types of thermal anomaly patterns observed in Mediterranean areas and rainfall amounts in the African and Indian monsoon regions at the inter-decadal (>10 years), inter-annual (<10 years), intra-seasonal (>10 d) and synoptic (3-9 d) scales through composite and correlation analyses performed on different atmospheric reanalyses and outgoing longwave radiation OLR data. The results show that the warmest situations registered over the whole Mediterranean Sea are concomitant of higher amounts in the African and Indian monsoon regions, contributing therefore to a positive African/Indian correlation. By contrast this correlation reverses when thermal variations between the eastern and western Mediterranean basins are considered: One observes higher African (lower Indian) rainfall with southwesterly (northeasterly) wind anomalies and an enhancement of the 3-9 d wave activity over the African continent associated with a northeastward extension of the main African Easterly Jet axis that favours wind shear and African easterly wave activity in the mid troposphere. More generally, eastern Mediterranean warming is synchronous of multiple atmospheric signals consistent with an intensification of moist convection, mid-level ascents and integrated moisture content in the atmospheric column over Africa. The reverse is observed in Indian regions and appears compatible with the Rodwell-Hoskins mechanism.
Keywords: African Research